Seroprevalence of pathogenic Leptospira serovars in hunting dog in Bosnia and Herzegovina - Ćutuk, Amel; Čengić, Benjamin; Velić, Lejla; Dovč, Alenka; Lindtner-Knific, Renata; Šaljić, Ermin; Bejdić, Pamela (2020)
Leptospirosis is an acute, subacute and chronical contagious disease of animals and humans. Causative agents of this disease belong to the genus Leptospira, family Leptospiraca. As a disease of wild animals, leptospirosis is widespread through Europe. Certain wild animals (rodents, fox and wild boars) are important reservoirs and highly probable vectors for the spread of infection into domestic animals and humans. During the hunting season, hunting dogs are often in direct or indirect contact with wild animals that could be carriers of this disease, and the possibility of appearance and spreading within this cohort of dogs is very high. The main reasons for this study on the prevalence of Leptospirosis in Bosnia and Herzegovina are the regular contact between hunting dogs and wild animals (carriers), and the lack of dataaboutLeptospirosisinhuntingdogs.In total, 175 serum samples from 15 towns of Bosnia and Herzegovina were tested. Twelve serovars of L. interrogans were used in the microscopic agglutination test. Presence of antibodies of four serovars was confirmed. Prevalence of seropositive dogs was 15.4% (27/175). Most positive dogs had a reaction to the Pomona serovar 51.8% (n=14), while the prevalence of the Sejroe serovar was 33.3%, Icterohaemorrhagiae serovar 11.1% and Bratislava serovar 3.7%. The highest number of positive reactions 55.5% (n=15) was with serum dilution of 1:200. This study showed that most infections in dogs were caused by serovars that are currently not included in commercial vaccines. One of the most efficient preventive measure could be vaccination with the serovars most often found in wild animals, as they appear to be the most common source of the infection.
Leptospiroza je akutna, subakutna i kronična zarazna bolest životinja i ljudi. Uzročnici ove bolesti pripadaju rodu Leptospira, porodici Leptospiraca. Leptospiroza kao bolest divljih životinja široko je rasprostranjena u Europi. Određene divlje životinje (glodavci, lisice i divlje svinje) kao važan rezervoar i vrlo vjerojatan vektor zaraze proširile su bolest na domaće životinje i ljude. Lovački psi tijekom sezone lova često su u direktnom ili indirektnom kontaktu s divljim životinjama koje bi mogle biti nositelji ove bolesti, a mogućnost pojave i širenja unutar kategorije takvih pasa vrlo je velika. Glavni razlozi ove studije o učestalosti leptospiroze na području Bosne i Hercegovine su redoviti kontakti lovačkih pasa i divljih životinja (nositelji) i nedovoljni podatci o prisutnosti leptospiroze u kategoriji lovačkih pasa. Ukupno je istraženo 175 uzoraka seruma iz 15 gradova Bosne i Hercegovine. U mikroskopskom testu aglutinacije korišteno je dvanaest serovara L. Interrogans. Potvrđena je prisutnost antitijela na četiri serovara. Prevalencija seropozitivnih pasa bila je 15,4 % (27/175). Većina pozitivnih pasa imala je reakciju na serovar Pomona 51,8 % (n=14), dok je u serovaru Sejroe prevalencija 33,3 %, serovar Icterohaemorrhagiae 11,1 % i serovar Bratislava 3,7 %. Najveći broj pozitivnih reakcija bio je s razrjeđivanjem seruma od 1:200 ili 55,5 % (n=15). Studije pokazuju da su većinu infekcija u pasa prouzročili serovari koji nisu uključeni u komercijalna cjepiva. Jedna od najučinkovitijih preventivnih mjera mogla bi biti cijepljenje sa serovarovima koji se najčešće nalaze u divljih životinja jer su one najčešći izvor zaraze.
Bibliografija: 21 jed.
Summary ; Sažetak.
Keywords: Psi -- Lovački psi -- Leptospiroza -- Serovari -- Prevalencija; Bosna i Hercegovina